Dukungan Kader kepada Orang dengan Gangguan Jiwa - Yesti Permata; Solikhah Solikhah; Dyah Suryani (Universitas Ahmad Dahlan, 2022)
Background: People with mental disorders (PwMD) are people who experience disturbances in thoughts, behaviour and feelings that cause suffering and obstacles in carrying out their functions as humans. Cadres or health workers acted as liaison between PwMD and health care facilities to overcome challenges faced by PwMD by providing several types of social supports. The purpose of this study was to describe the support of cadres to PwMD in the working area of Ponjong I Public Health Center. Objective: The purpose of this study was to describe the support of cadres to PwMD in the working area of Ponjong I Public Health Center. Methods: This study used a cross-sectional design with a sample of 177 cadres. The data were analyzed as a percentage of the characteristics and several types of social support namely emotional, informational, instrumental and appraisal support. Results: A total of 177 cadres aged 41-65 years were 59.89%. The total of social support from cadres categorized as good (85.31%), while the percentages according to their dimensions are 50.3% for informational support, 49.2% for appraisal support, 49.7% for emotional support and 47.5% for instrumental support. Conclusions: The social support provided by cadres for PwMD was cat-egorized as good with more prominent dimensions of appraisal and emotional support. Dimensions of social support that still needs to be optimized are providing informational and instrumental supports.